Makna Ukhuwah dalam Al-Qur'an: Studi Komparatif antara Tafsir Ibnu Katsir dan Tafsir Al-Munir - Febriyanti, Dini; Safi'i, Mohamad; Isyanto, Nur (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2024)
This article discusses the meaning of ukhuwah in the Qur'an through a comparative study approach between the tafsir of Ibn Katsir and the tafsir of Al-Munir. The main focus of this research is to identify the views of each interpretation on the concept of ukhuwah in the context of the Qur'an. The method used is a comparative analysis of the verses of the Qur'an that directly or indirectly discuss the theme of ukhuwah, with reference to the interpretation of Ibn Katsir and Al-Munir. The results of the study show that the two interpretations have different approaches in explaining the meaning of ukhuwah. The tafsir of Ibn Katsir tends to emphasize the aspects of brotherhood and unity of the ummah in a broader context, while the tafsir of Al-Munir emphasizes more on the dimensions of togetherness, mutual help, and harmony in the Muslim community. In conclusion, although there are differences in approaches in explaining ukhuwah, the two interpretations provide a deep understanding of the importance of solidarity and good relations between fellow Muslims in accordance with the teachings of the Qur'an. This study contributes to a deeper understanding of the concept of ukhuwah in different perspectives of Qur'an interpretation.